IS SOCIAL MEDIA MAKING US LESS SOCIAL? (Ustozlar uchun, 2025)
The advent and widespread adoption of social media platforms have profoundly reshaped the landscape of human interaction. This paper explores the complex question of whether social media is leading to a decrease in genuine human sociability or merely transforming its nature. We argue that the impact is multifaceted, defying a simple binary answer. While some perspectives suggest that social media fosters superficial connections, reduces face-to-face interaction, and contributes to feelings of loneliness and anxiety, others highlight its capacity to maintain distant relationships, build communities around shared interests, provide social support, and facilitate real-world engagement. The ultimate effect often hinges on individual usage patterns, the quality of digital engagement, and pre-existing social predispositions. Understanding this intricate relationship is crucial for navigating the digital age mindfully and fostering healthier social connections.